2016
DOI: 10.21093/di.v16i2.311
|View full text |Cite
|
Sign up to set email alerts
|

EFL Students’ Preferences toward the Lecturer’s Corrective Feedback in Business Letters Writing

Abstract: This study aimed to investigate; the students' preferences toward the lecturer's corrective feedback in the business letter writing and their reasons why they preferred for particular corrective feedback types. A case study was used by involving 15 EFL students who enrolled the Business Correspondence Course. The questionnaire and interview were used as the research instruments. This study revealed that; (1) the students preferred to receive lecturer correction (M=5.00), followed by lecturer-students conferenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
(34 reference statements)
2
2
0
Order By: Relevance
“…97 % of respondents indicate a positive attitude toward receiving feedback on their writing skills in seven different areas, namely language, organization/structure/mechanics, vocabulary, content, grammar, conciseness, and writing goal. This finding aligns with the findings of Sanu's (2016) investigation that revealed a predilection among Indonesian students for the receipt of the accurate version over the erroneous form. Moreover, it is also supported by Black and Nanni (2016), whose study on English as a Foreign Language (EFL) Thai students demonstrated a preference for direct feedback accompanied by metalinguistic commentary, underscoring the overarching significance accorded to precision in language accuracy by the students.…”
Section: It Would Be Nice If You Corrected It While Writing Down the ...supporting
confidence: 90%
“…97 % of respondents indicate a positive attitude toward receiving feedback on their writing skills in seven different areas, namely language, organization/structure/mechanics, vocabulary, content, grammar, conciseness, and writing goal. This finding aligns with the findings of Sanu's (2016) investigation that revealed a predilection among Indonesian students for the receipt of the accurate version over the erroneous form. Moreover, it is also supported by Black and Nanni (2016), whose study on English as a Foreign Language (EFL) Thai students demonstrated a preference for direct feedback accompanied by metalinguistic commentary, underscoring the overarching significance accorded to precision in language accuracy by the students.…”
Section: It Would Be Nice If You Corrected It While Writing Down the ...supporting
confidence: 90%
“…The student preference for and reliance on teacher error correction in writing as found in this study is similar to what Ha and L. T. Nguyen (2021) found about Vietnamese EFL students' preference for teacher oral correction. This finding is also consistent with Sanu (2016) who revealed that, in an Indonesian context, teacher-generated correction was found to be the most preferred type of error correction with peer correction and self-correction the least.…”
Section: Learners' Previous Experiences and Practices Regarding Error...supporting
confidence: 90%
“…In support with Rezaei & Jafari (2014), Ariyanti (2017), and Ahmadi et al (2012), Sanu (2016) also had a research on feedback used by a lecturer towards students' business letters writing where he explored the students' preferences towards the feedback given by the lecturer. In his research, he found that lecturerstudents conferencing is at the top of student's preference to correct their writing because they got appreciation both from the lecturer and other friends as well as knowing their weaknesses in writing the business letters as a class.…”
Section: Introductionmentioning
confidence: 99%
“…Relying on above theories and studies from several researchers, this study is aimed to explore the perception as well as the preference of EFL students from Widya Gama Mahakam University, Samarinda, Indonesia, towards their lecturer's teaching writing method. Unlike with Sanu (2016), this study focuses more on traditional and e-feedback used by the lecturer to have comments on the students' essay, where previously the researchers ensured to the lecturer of what kind of methods she usually used in teaching English essay writing. The further expectation of this research is the researchers can explore what kind of e-learning media she applied in the classroom.…”
Section: Introductionmentioning
confidence: 99%